PENGEMBANGAN MEDIA PEMBELAJARAN PAPAN KOSA KATA DI KELAS III SDN 308 RANTAU SULI - Eka Filahanasari; Lili Nopa Sari; Melisa Anggrayni (STKIP Subang, 2023)
Education is the need of every individual and always changes according to the times, science, technology and culture of society. Education is very important in improving the quality of human resources. In study the authors are interested in developing vocabulary board learning media because there are still many students who find it difficult to read. The research method used author this research is (research and development) or what is known the ADDIE development model. This model consists of 5 stages, namely: Analyze, design, Developnet, implementation. Evaluation. The type of data taken this study is quantitative data and quantitative data. The instrument used in this study is validation questionnaire, practicality and effectiveness. Data collection techniques used interview techniques, questionnaires and documentation. Data analysis techniques used are media validation analysis techniques, media practicality analysis and media effectiveness analysis. The results obtained The validity of the vocabulary board learning media as assessed the validator totaled 3 people, indicating vocabulary board learning media obtained a percentage of 89.8% in a very valid category, the vocabulary board learning media is feasible to use and in accordance with the provisions of SDN 308 /VI Rantau Suli. The results of practicality assessed from the teacher response questionnaire and student response questionnaire to the vocabulary board learning media obtained the following percentages: 94% teacher response questionnaire in very practical category, 100% student response questionnaire in very practical category. For the results of the effectiveness assessed from the results of the test questions, it obtained a percentage of 85.2% in the very effective category.